2007
DOI: 10.1002/mnfr.200600164
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols as anticancer compounds

Abstract: Phytochemicals have been proposed to offer protection against a variety of chronic ailments including cardiovascular diseases, obesity, diabetes, and cancer. As for cancer protection, it has been estimated that diets rich in phytochemicals can significantly reduce cancer risk by as much as 20%. Phytosterols are specific phytochemicals that resemble cholesterol in structure but are found exclusively in plants. Phytosterols are absorbed from the diet in small but significant amounts. Epidemiological data suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(194 citation statements)
references
References 73 publications
(76 reference statements)
3
183
0
2
Order By: Relevance
“…The reduction of liver lipids is beneficial to liver function by restoring hepatocyte morphology and reduction of liver steatosis [26]. Published data indicated that BBR and PS, when administered alone, have beneficial effects on the immune function [62][63][64][65][66]. As it was not measured in the current study, it is not clear whether reduced spleen weight by the combined treatment of BBRPS influences the immune function.…”
Section: Discussionmentioning
confidence: 65%
“…The reduction of liver lipids is beneficial to liver function by restoring hepatocyte morphology and reduction of liver steatosis [26]. Published data indicated that BBR and PS, when administered alone, have beneficial effects on the immune function [62][63][64][65][66]. As it was not measured in the current study, it is not clear whether reduced spleen weight by the combined treatment of BBRPS influences the immune function.…”
Section: Discussionmentioning
confidence: 65%
“…Ellagic acid (EA) is a natural dietary polyphenol whose benefits in a variety of diseases shown in epidemiological and experimental studies involve anti-inflammation, antiproliferation, anti-angiogenesis, anti-carcinogenesis and antioxidation properties (Kim et al 2013). β-sitosterol (BS) and stigmasterol (SS), phytosterols found in plant foods especially plant oils, seeds and nuts, cereals and legumes (Muti et al 2003) that resemble cholesterol both in structure and biological function (Bradford and Awad 2007). Phytosterols have been added to food matrices other than fat spread including low-fat milk, bakery products, orange juices, cereal bars, low fat beverages and chocolate bars (Jones and AbuMweis 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their cholesterol-lowering actions, mounting evidence suggests that phytosterols possess anti-cancer effects against a number of different types of cancers (126)(127)(128)(129)(130)(131)(132). Phytosterols seem to act through multiple mechanisms of action, including inhibition of carcinogen production, cancer-cell growth, angiogenesis, invasion and metastasis, and through the promotion of apoptosis of cancerous cells.…”
Section: Anti-cancer Effects Of Phytosterolsmentioning
confidence: 99%